Erlyna Tri Rohmiatun ANALISIS RATIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN (STUDI KASUS PADA PT. ASTRA AGRO LESTARI TBK YANG TERDAFTAR DI BEI PERIODE 2014-2018) : Program Studi Akuntansi, Universitas Nahdlatul Ulama Sidoarjo *e-mail: erlynatri.akn@unusida.ac.id - Erlyna Tri Rohmiatun (GREENOMIKA, 2019)
The purpose of this study was to determine the financial performance of PT. Astra Agro Lestari, Tbk based on liquidity, leverage, activity and profitability ratio analysis. The type of research used in this study is the description and research method used is quantitative because there are numbers and calculations using formulas. The results of the study can be seen that the overall liquidity ratio is still below the industry standard. This shows that the company is not safe in the short term. Overall leverage ratios do not meet industry standards, this shows companies are able to manage assets well and reduce funding using debt. The overall activity ratio of the company is not above the standard, but the reve-able turnover is above the standard. The overall profitability ratio is below the standard. The company is not maximized in revenue from sales.